The Merry Adventures of Robin Hood - Pyle, Howard, 1853-1911 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Merry Adventures of Robin Hood" by Howard Pyle is a novel published in 1883. Pyle weaves traditional Robin Hood ballads into a unified story, following the legendary outlaw as he gathers his Merry Men and battles corrupt authorities in Nottinghamshire. Through episodes featuring Little John, Friar Tuck, and Allan a Dale, Robin emerges as a heroic figure who aids the poor and resists injustice. This influential retelling transformed Robin Hood into a beloved champion of the common people for generations to come. (This is an automatically generated summary.)
Preface: from the author to the reader -- How Robin Hood came to be an outlaw -- Robin Hood and the tinker -- The shooting-match at Nottingham town -- Will Stutely rescued by his good companions -- Robin Hood turns butcher -- Little john goes to Nottingham fair -- How Little John lived at the sheriff's -- Little John and the tanner of Blyth -- Robin Hood and Will Scarlet -- The adventure with Midge the miller's son -- Robin Hood and Allan a Dale -- Robin seeketh the Curtal Friar -- Robin Hood compasses a marriage -- Robin Hood aids a sorrowful knight -- How Sir Richard of the Lea paid his debts -- Little John turns barefoot friar -- Robin Hood turns beggar -- Robin Hood shoots before Queen Eleanor -- The chase of Robin Hood -- Robin Hood and Guy of Gisbourne -- King Richard comes to Sherwood Forest -- Epilogue.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Merry_Adventures_of_Robin_Hood
Release date is 2006-02-05
Produced by Charles Keller and David Widger
Keywords: Folklore -- England; Robin Hood (Legendary character) -- Legends